2006
DOI: 10.1111/j.1365-2729.2006.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing an effective support system for inquiry learning in a Web‐based environment

Abstract: Sixty-five teams of basic and secondary school students solved problem-solving tasks during a virtual hike in a Web-based inquiry-learning simulation 'Hiking Across Estonia'. This environment provided learners with all necessary background information for problemsolving and tools for carrying out experiments. There were 25 tasks in certain order about ecological and environmental issues. The teams were clustered according to the data about participants, the results of the pre-and post-test, and their achieveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 26 publications
3
40
0
6
Order By: Relevance
“…De Jong & van Joolingen (1998) defined it as an educational strategy based on discovering knowledge that fosters active participation and learners' responsibility. Pedaste & Sarapuu (2006) referred to inquiry-based learning as an approach in which learners solve problems by using their inquiry skills. Recently, inquirybased learning has been increasingly suggested as an efficient approach for fostering students' curiosity and motivation by linking science teaching in schools with informal learning and phenomena in everyday life (Specht, Bedek, Duval, & Held, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…De Jong & van Joolingen (1998) defined it as an educational strategy based on discovering knowledge that fosters active participation and learners' responsibility. Pedaste & Sarapuu (2006) referred to inquiry-based learning as an approach in which learners solve problems by using their inquiry skills. Recently, inquirybased learning has been increasingly suggested as an efficient approach for fostering students' curiosity and motivation by linking science teaching in schools with informal learning and phenomena in everyday life (Specht, Bedek, Duval, & Held, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, web-based learning systems can be designed to provide tools to enhance structured learning opportunities and enhance learning (Pedaste & Sarapuu, 2006). Tools such as handheld computers can also be used to enhance student learning and performance in classrooms (Kuhlman, Danielson, Campbell, & Topp, 2006).…”
Section: Trend 6-learning Is Moving Beyond and Between Nation Statesmentioning
confidence: 99%
“…Pedaste and Sarapuu [9] have already shown that multiple factors, for instance the initial level of problem-solving skills of learners, influence outcomes of solving problems in a web-based learning environment. This study demonstrates that initial level of visual analysis skills is also an important factor influencing the student performances in virtual learning environments.…”
Section: Relationship Between Visual Analysis Skills and Modelling Acmentioning
confidence: 99%